Community and facility-level barriers to achieving UHC in Kono District, Sierra Leone and Maryland County, Liberia. - Julia Higgins; Jean Gregory Jerome; Foday Boima; Emily Dally; Luke Krangar; Emma Jean Boley; Sterman Toussaint; Yusupha Dibba; Chiyembekezo Kachimanga; Michael Mhango; Vivian Chung; Samuel Watson; et al. (Public Library of Science (PLoS), 2023)
Universal Health Coverage (UHC) is achieved when individuals and communities receive the health services they need without suffering financial hardship. However, many countries face barriers to building health systems that enable the availability of affordable, accessible care. The goal of this study was to present a model of local monitoring of barriers and to provide a roadmap for designing interventions that improve access to and use of healthcare delivery systems. We conducted household, individual, and health facility surveys in seven catchment areas in Sierra Leone and Liberia between December 2019 and March 2020. A two-stage cluster sampling method was used to sample households and individuals, and all health facilities were included. We divide access barriers into demand (patient-side care seeking behavior), supply (availability of facilities and services), and their intersection (affordability, spending, and use rates). Among the 2,576 respondents within our 1,051 surveyed households, the propensity to seek care when ill was reported at 90% in Sierra Leone (n = 1,283) and 70% in Liberia (n = 806). We estimated that 31% of households spent greater than 10% of their total expenditure on healthcare in a month, and that 14.5% of households spent greater than 25%. Overall, the general service readiness index mean score for all health centers was around 70%. The greatest hindrance to service readiness was the availability of essential medicines, with facilities reporting an average score of 32% in Sierra Leone and 63% in Liberia. Our evidence suggests that the cost of care is both a barrier to care-seeking and a persisting problem among care-seeking patients. Lack of service availability (essential equipment and medicines), poses a risk to high-quality care. The research team recommends deploying interventions (visit cost subsidies, supply chain improvements) targeted at resolving these issues in order to advance the goal of achieving UHC.